A Study to Compare Efficacy of Oral Baclofen versus Oral Tizanidine in Post-stroke Spasticity of Upper Limb - Ankita Singha Roy; Sudipan Mitra; Subhasish Pati; Sagnik Mukherjee (Indian Journal of Physical Medicine & Rehabilitation)
Introduction: Spasticity is a common complication that occurs after stroke and results in significant loss of functional ability. Hence, a study was planned to compare the efficacy of oral baclofen versus oral tizanidine in post-stroke spasticity amelioration and improvement of upper limb function. Materials and Methods: The study was conducted in the Department of Physical Medicine and Rehabilitation in a tertiary care hospital in West Bengal for 6 months. It was an observational prospective analytical study. The patients with stroke who presented with spasticity and fulfilled the inclusion and exclusion criteria and gave their consent for the study were included in the study. The sample size of the study was 28. One group (Group 0) received oral baclofen at a dose of 10–40 mg and the other group (Group 1) received oral tizanidine at a dose of 4–12 mg. The outcome measures were calculated using the Modified Ashworth Scale (MAS) score for reduction in spasticity and the Action Research Arm Test (ARAT) score for improvement in upper limb function. Patients were followed up after 1, 2 and 6 months, and MAS and ARAT scores were compared with baseline values. Results: In the baclofen group, for elbow spasticity, the most notable change occurred between MAS 3 (4th visit at 6 months) and MAS 0 (1st visit), with a highly significant mean rank difference (adjusted P < 0.001). Similar trends were observed in the tizanidine group, with significant differences between MAS 3 and MAS 0 (adjusted P < 0.001). For wrist flexor spasticity in the baclofen group, the median MAS 0 score was 2 (interquartile range [IQR]: 1.5–3). The tizanidine group also showed a median MAS 0 score of 2 (IQR: 1.5–2). Scores for both groups decreased over time. The P value was significant (<0.05) showing that the MAS scores for wrist changed over time in both the groups. The baclofen group showed a higher median ARAT score of 39.5 (IQR: 23.5–40.5), ranging from 20 to 57 at 6-month follow-up visit, compared to the tizanidine group, which had a median score of 29 (IQR: 24–32.5) and a range of 22–44. However, this difference between the groups, while numerically larger, was not statistically significant (P = 0.196). Conclusion: Both oral baclofen and oral tizanidine have been found to have similar efficacy in the management of post-stroke spasticity.